2005
DOI: 10.1136/vr.156.13.401
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of experimental bovine spongiform encephalopathy: preclinical infectivity in tonsil and observations on the distribution of lingual tonsil in slaughtered cattle

Abstract: The infectivity in tissues from cattle exposed orally to the agent of BSE was assayed by the intracerebral inoculation of cattle. In addition to the infectivity in the central nervous system and distal ileum at stages of pathogenesis previously indicated by mouse bioassay, traces of infectivity were found in the palatine tonsil of cattle killed 10 months after exposure. Because the infectivity may therefore be present throughout the tonsils in cattle infected with BSE, observations were made of the anatomical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 11 publications
5
119
1
1
Order By: Relevance
“…In cattle with BSE, no other sites of agent replication or PrP Sc accumulation have been found in the lymphoid tissues apart from the GALT tissues of the Peyer's patches in the ileum and the tonsil of experimentally infected animals [11,16,20,32,[72][73][74]. Infectivity is also not detectable in the blood of BSE affected cows with the mouse bio-assay [16,72].…”
Section: Draining To the Galt Lymph Nodes And Lymphatic/haematogenic mentioning
confidence: 98%
See 1 more Smart Citation
“…In cattle with BSE, no other sites of agent replication or PrP Sc accumulation have been found in the lymphoid tissues apart from the GALT tissues of the Peyer's patches in the ileum and the tonsil of experimentally infected animals [11,16,20,32,[72][73][74]. Infectivity is also not detectable in the blood of BSE affected cows with the mouse bio-assay [16,72].…”
Section: Draining To the Galt Lymph Nodes And Lymphatic/haematogenic mentioning
confidence: 98%
“…In cattle experimentally infected with a high oral dose of BSE, infectivity was present in the ileum six months after oral infection [71,73] and in the tonsil ten months after oral infection (the latter only detectable using the more sensitive bovine transgenic mouse and cattle bioassay) [16,74]. In these animals PrP Sc was immunohistochemically detected in TBM of the ileal Peyer's patches but not in the tonsil [26,63,74]. Despite this apparently low involvement of the lymphoid system, neuroinvasion still occurs after a relatively long incubation period.…”
Section: In Naturally Infected Bse Cases No Prpmentioning
confidence: 99%
“…In bovine tuberculosis (Cassidy et al, 1999), and bovine spongiform encephalopathy (BSE; Wells et al, 2005) tonsils may serve as a port of entry for pathogens. Ruminants have less extensive RTALT than other species and the pharyngeal tonsil has been described as the major component of RTALT in cattle and sheep (Anderson et al, 1986;Chen et al, 1989;Schuh and Oliphant, 1992;Liebler-Tenorio and Pabst, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, EC Regulation 999/2001 specifies that the tongue be cut at the lingual torus of the basihyoid bone to avoid food contamination by lingual tonsils. Wells et al [11] reported that intracerebral inoculation of palatine tonsils of cattle experimentally infected orally with BSE ten months earlier caused BSE infection in other cattle. They also pointed out the possibility that tonsils in general are infective.…”
Section: Discussionmentioning
confidence: 99%